Dampak Aplikasi Mulsa terhadap Dominasi dan Pertumbuhan Gulma pada Edamame - Destieka Ahyuni; Dulbari Dulbari; Hidayat Saputra; Lina Budiarti; Miranda Ferwita Sari (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2021)
Edamame was a commodity that contains all types of essential amino acids that can stabilize blood sugar levels, increase metabolism and energy levels, and help build muscle and immune system cells. Farmer’s interest in planting edamame is high due to the high demand and promising commodity prices. However, edamame is often faced with weed disturbances. The weeds in edamame cultivation can reduce production in quantity and quality. Research is needed for effective weed control techniques to reduce losses and increase production plus increasing income. The research was conducted at the Lampung State Polytechnic from April to September 2020. The study was arranged using a randomized block design with single factor treatment in the form of weed control techniques with 4 treatments and 3 replications. The aim of this research was to find the best weed control techniques in edamame cultivation. The results of this study were using mulch can reduce weed growth by 75.75% to 95.45% compared without using mulch. The highest pressure on weed growth was obtained from the used plastic mulch as a weed control technique.